The Levels of Student Questioning and Critical Thinking Ability in Acid-Base Topics and Correlation with Learning Outcomes - Magfirah Magfirah; Zulhan Zulhan; Tri Santoso; Afadil Afadil; Sri H. V. Pulukadang; Meida E. Marpaung (Universitas Tadulako, 2025)
Acid-base material is often considered difficult for students because it is abstract, leading to misconceptions and poor learning outcomes. The ability to ask questions reflects cognitive engagement and is closely related to the critical thinking required to understand abstract concepts. Therefore, it is important to examine this skill to obtain evidence of its role in improving chemistry learning outcomes and as a consideration for teachers in determining the appropriate learning process. This study aims to analyze students' questioning skills and critical thinking abilities in acid-base learning and examine the relationship between these skills and students' learning outcomes. A quantitative descriptive approach was employed and conducted at SMAN 1 Dampal Utara. The research subjects comprised 30 students, including 17 females and 13 males. Male students. The sample was selected using a purposive sampling technique. The instruments used for data collection included the questioning skills test and the critical thinking skills test. The results indicated that students’ questioning skills were categorized as moderate with a percentage of 57.5 %, similarly, their critical thinking abilities also fell into the mild category with a rate of 48.33 %. Correlation analysis revealed a significant relationship between questioning skills and learning outcomes (r= 0.386;α=0.035). Meanwhile, the relationship between critical thinking and learning outcomes was shown to be insignificant (r= 0.225;α= 0.173). These findings suggest that questioning skills can contribute to optimal learning outcomes.